Revealing The Socio-Cultural Perspective Of Madurese Community On Tax Avoidance In Government Agencies - Moh Riskiyadi (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to obtain an overview of tax avoidance in government agencies based on the socio-cultural habits of the community. This study uses a qualitative realist ethnographic method to reveal an overview of tax avoidance in government agencies in Madura with the supplier and treasurer informants. The results obtained indicate that tax avoidance in government agencies is influenced by the cultural habit of repaying the kindness of others with kindness in kind. The habit of not being indebted for the kindness of others becomes a factor of pressure as well as a justification for tax avoidance by splitting proof of expenditure. The opportunity factor that the treasurer has as a central figure in financial management, supported by the provision of split proof of expenditure by suppliers, is a driving factor for tax avoidance in government agencies. The implication of this research is to provide an overview of the causes and modes of tax avoidance in government agencies, so that appropriate tax regulations and supervision can be formed to minimize the occurrence of tax avoidance.